Regional analysis of myelin basic protein across postnatal brain development of C57BL/6J mice - Ozarkar, Siddhi S.; Patel, Ridthi K. R.; Vulli, Tasmai; Friar, Carlee A.; Burette, Alain C.; Philpot, Benjamin D. (Frontiers in Neuroanatomy, 2025)
Healthy brain development hinges on proper myelination, with disruption contributing to a wide array of neurological disorders. Immunohistochemical analysis of myelin basic protein (MBP) is a fundamental technique for investigating myelination and related disorders. However, despite decades of MBP research, detailed accounts of normal MBP progression in the developing mouse brain have been lacking. This study aims to address this gap by providing a detailed spatiotemporal account of MBP distribution across 13 developmental ages from postnatal day 2 to 60. We used an optimized immunohistochemistry protocol to overcome the challenges of myelin’s unique lipid-rich composition, enabling more consistent staining across diverse brain structures and developmental stages, offering a robust baseline for typical myelination patterns, and enabling comparisons with pathological models. To support and potentially accelerate research into myelination disorders, we have made >1,400 high-resolution micrographs accessible online under the Creative Commons license.